Functional role of red (retro)-carotenoids as passive light filters in the leaves of Buxus sempervirens L. increased protection of photosynthetic tissues? - Hormaetxe, Koldobika (Journal of experimental botany, 2005)
Red (retro)-carotenoids accumulate in chloroplasts of Buxus sempervirens leaves during the process of winter leaf acclimation. As a result of their irregular presence, different leaf colour phenotypes can be found simultaneously in the same location. Five different colour phenotypes (green, brown, red, orange, and yellow), with a distinct pattern of pigment distribution and concentration, have been characterized. Leaf reddening due to the presence of anthocyanins or carotenoids, is a process frequently observed in plant species under photoinhibitory situations. Two main hypotheses have been proposed to explain the function of such colour change: antioxidative protection exerted by red-coloured molecules, and green light filtering. The potential photoprotective role of red (retro-) carotenoids as light filters was tested in Buxus sempervirens leaves. In shade leaves of this species the upper (adaxial) mesophyll of the lamina was replaced by the equivalent upper part of a different colour phenotype. These hybrid leaves were exposed to a photoinhibitory treatment in order to compare the photoprotective effect exerted by adaxial parts of phenotypes with a different proportion of red (retro)-carotenoids in the lower mesophyll of a shade leaf. The results indicated that the presence of red (retro)-carotenoids in the upper mesophyll did not increase photoprotection of the lower mesophyll when compared with chlorophyll, and the best protection was achieved by an upper green layer. This was due to the fact that the extent of photoinhibition was proportional to the amount of red light transmitted by the upper mesophyll and/or to the chlorophyll pool located above. These results do not exclude a protective function of carotenoids in the upper leaf layer, but imply that, at least under the conditions of this experiment, the accumulation of red pigments in the outer leaf layers does not increase photoprotection in the lower mesophyll